STUDI LITERATUR REVIEW FAKTOR YANG BERHUBUNGAN TERHADAP KEJADIAN MUSCULOSCELETAL DISORDERS (MSDs) PADA PETANI - Dian Purnama Sari; Desi Rambe, Alfiza Putri Rahmadillah, Helma Denisa Harahap, Ramayani Anwar Harahap, Viona Afiqah (Jurnal Kesehatan, 2023)
Farming is a job that is done in a wet area (mud). Farmers who do this work are not only men but women too, so it is possible that work accidents will occur. An injury experienced by a farmer that attacks the nerves, joints, ligaments, tendons and parts of the body as a support such as the neck and back. The consequences of the work done are called musculoskeletal disorders (MSDs). This disease can occur if the demands of the work given are not in accordance with the physical abilities of the individual's body. This study uses a type of descriptive analysis. The method used is a litirature study with the aim of analyzing the factors that cause musculoskeletal disorders (MSDs) in farmers. A search for literature was carried out online, namely through Google Scholar, scholars, and found 5 national articles. Articles are then analyzed and processed with the stages of organizing, synthesizing, identifying and further analysis so that answers to the problem formulation are found. The results of this study indicate that individual factors (gender, age, years of service), work factors (workload, posture, duration of work, repetitive movements, handling materials manually) environmental factors (work area,) this can lead to incidents MSDs in farmers. Occupational factors and environmental factors are closely related to the occurrence of Musculoskeletal Disorders (MSDs), namely age, body mass index, years of service.